Kelainan Ventrikel Tunggal Pada Anak - Isabel Theodora Simangunsong; M Marliando Satria Pangestu Catur (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Single ventricle or univentricular heart is a congenital heart disease which is complex, it is characterized by in which one ventricle is severely unwell developed or hypoplastic. Single ventricle is classified into classes depends on the morphology with the most common form is the Hypoplastic Left Heart Syndrome (HLHS) which happen in 2-3 neonates per 10.000 live births. The method used in this article is literature review from various national and international journals. There is no specific etiology for this defect, but it is suggested that environmental factors and genetics has a role and for this reason, it is necessary to do the prenatal diagnosis that affects neonatal morbidity and mortality. This condition results the tempering of oxygenated blood with deoxygenated blood. Single ventricle is universally fatal if it’s untreated, palliative surgery might be the best option to increase survival of the patients into adulthood. This palliative surgery contents three stages with the end result maximizing systemic blood oxygenation by changing blood flow from parallel to serial circuits and to maintain ventricular systemic functionality. Fontan procedure has shown the increase of the survival rate until 70%.